The relations between the Holy See and Spain during the period of Serrano Súñer - Martín de Santa Olalla Saludes, Pablo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
The relations between the Holy See and Spain during General Franco’s dictatorship were more difficult as it could be thought, because of the force of fascist forces in spanish politics. The strong man of first Franco’s government after Spanish Civil War, Ramón Serrano Súñer, had to work hard to get agreements with Pope Pío XII, who didn’t really trust him, because of his excelent relations with the Germany of Adolf Hitler and the Italy of Benito Mussolini. This article studies the role of the spanish ambassador, José Yanguas Messía, during the years 1938-42, and how he got for his government the privilege of presentation for bishops in benefit of the Chief of State, General Francisco Franco.
Keywords: Holy See; dictatorship; fascism; bishops